Effects of rf power on the structural properties of carbon nitride thin films prepared by plasma enhanced chemical vapour deposition - Othman, Maisara; Ritikos, Richard; Khanis, Noor Hamizah; Rashid, Nur Maisarah Abdul; Rahman, Saadah Abdul; Gani, Siti Meriam Ab; Muhamad, Muhamad Rasat (Elsevier, 2011)
Carbon nitride (CR(x)) thin films were deposited by radio frequency plasma enhanced chemical vapour deposition (rfPECVD) technique from a gas mixture of methane (CH(4)), hydrogen (H(2)) and nitrogen (N(2)). The effects of rf power on the structural properties of CN(x) thin films were discussed in this paper. It was found that rf power had significant effects on the growth rate, structural and morphological properties of the deposited films. The point of transition of the growth rate trend marked the equilibrium condition for primary and secondary reactions in growth kinetics of the film with respect to rf power. The films grown at this optimum rf power were most ordered in structure with high surface roughness and had the lowest N incorporation. This work showed that H etching effects and ion bombardment effects increase with increase in rf power and strongly influenced the structure of the CN(x) films. (C) 2011 Elsevier B.V. All rights reserved.